Experimental study on retrofit of school buildings by adding sandwich columns to partition brick walls. - Chung, L. L. (Earthquake engineering & structural dynamics.)
Thousands of buildings were damaged by the devastating Chi-Chi earthquake on September 21, 1999. Of all the public buildings, school buildings are the most vulnerable to earthquake damage, and the retrofitting of existing school buildings becomes a stringent issue. In addition to cost effectiveness, the impact of retrofitting methonds on the functions of the school buildings needs to be considered. This paper therefore proposes the retrofitting of school buildings by adding sandwich columns onto partition brick walls. The sandwich column is divided into two parts and is added to the two sides of the partition brick wall held with pairs of U-shaped bars. The retrofit does not require the removal of windows or doors in the longitudinal direction making the proposed method cost effective and minimizes the impact on the function of the school buildings. Five full scale specimens without and with retrofitting were designed and fabricated for testing based on the partition brick wall frames of the existing school buildings. The specimens were subjected to cyclic loading in the out of plane direction through a loading frame so that the columns deformed with double curvatures. The experimental results verified the feasibility of the proposed retrofit method. The data showed that the lateral strength of the retrofitted specimen doubled that which was not and that the residual strength of the retrofitted specimen was just as high as the ultimate strength of the specimen without retrofitting. The analytical results in lateral strength yielded conservative figures compared with experimental measurements.